UTILIZATION OF INDONESIA MARINE RESOURCES IN AN EFFORT TO REALIZE INDONESIA TOWARDS THE SHAFT OF THE MARITIME WORLD - Lathifah Hanim; MS Noorman (The 2nd Proceeding “Indonesia Clean of Corruption in 2020", 2020)
development Orientation that more attention to the mainland area needed to be changed in view of the sea is a source of livelihood in the future. Paradigm of development in the marine sector that holds tremendous natural wealth became a chore for the government to restore the glory of this nation as a maritime nation. Especially is to realize Indonesia to the shaft of the maritime world. Indonesian sea contains many diverse resources both renewable such as fisheries, coral reefs, mangrove forests, sea grass, and germplasm and others or resources that are not renewable, such as oil and gas, , mineral, and ocean energy such as waves, wind, and OTEC (Ocean Thermal Energy Conversion) is being developed today. The amount of the economic opportunities of the utilization of marine resources is so large it has been dully contributed greatly to the improvement of the nation's economy, also even it is fitting into the driving sector of the national economy is dominant. But in fact the fisheries and marine sector nationally is still not used optimally, it is shown from the data in plain view that coastal communities are communities closest to the coastal and marine resources is generally still classified as poor or categorized as a people with the welfare of the low , The formulation of his problem is how the utilization of Indonesia's marine wealth in an effort to realize the efforts of Indonesia towards the shaft of the maritime world? There are several factors that led to the use of the sea as a potential powerful nation was neglected among them are weak security, weak supervision, and weak coordination of the country. Actually, Indonesia has a Maritime Surveillance System (maritime surveillance systems) at a military institution whose domain is the sea. Our country needs to have a clear maritime policy and visionary as geopolitical concerns and basic policies on the management of marine resources. Policies concerning various breakthroughs to utilize marine resources in an optimal and sustainable competitive advantage as a nation. Keywords: Utilization of Ultra Marine, Maritime Shaft.